Tech timeline.
The first pocketable mobile phone, the Internet, music-to-go, the advances in electronic gaming, P2P downloading, and the amazing USB thumb drive. Here's how the past 20 years' worth of technology shaped the digital world we have today.
Keywords: Technology--History.